The Philosophy of Islamic Education in Strengthening Character Education in the Digital Era: A Case Study of MA Al Umm Malang - kholil, kholil; Lukman Hakim; Achmad Izzul Hisyam; Handri Hartanto; Khoiriyah (Al-Hikmah: International Journal of Islamic Studies, 2025)
This study aims to examine how Islamic educational philosophy is constructed and implemented in strengthening students’ character education in the digital era, as well as to formulate a conceptual model of character development grounded in Islamic values through a case study at MA Al Umm Malang. Addressing contemporary challenges such as ethical disorientation, value fragmentation, and declining self-regulation due to rapid digitalisation, this research employs a qualitative approach with an interpretive case study design. Data were collected through in-depth interviews, participant observation, and document analysis, and analysed thematically within the framework of Islamic educational philosophy. The findings indicate that character education at MA Al Umm Malang is rooted in a tauhidic, holistic, and adab-oriented philosophy, in which sound Islamic creed, noble character, and moral exemplarity serve as foundational elements. These values are operationalised through an integrated educational system, continuous mentoring, and value internalisation embedded in the 24-hour pesantren environment. Furthermore, this study formulates a conceptual model consisting of five interrelated components: a tauhidic value foundation, a holistic educational system, role modelling, sustained mentoring and evaluation, and epistemic reinforcement as a filter for digital ethics. The study concludes that effective character education in the digital era requires a strong Islamic philosophical foundation and coherent institutional implementation.